1999
DOI: 10.1016/s0022-5223(99)70320-x
|View full text |Cite
|
Sign up to set email alerts
|

Volume-outcome relationships in cardiovascular operations: New York state, 1990-1995

Abstract: The importance of these findings lies in the rather striking difference between the volume-outcome relationship found for operations for abdominal aortic aneurysms and congenital cardiac defects and the lack of such a relationship for coronary artery bypass grafting. This observation may be largely explained by the quality improvement program in New York State for bypass operations since 1989. If so, these results have important implications for expanding the scope of quality improvement efforts in New York St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 13 publications
4
69
1
1
Order By: Relevance
“…This finding supports and extends the results from Peterson et al (2004), Halm et al (2002, Luft et al (1987) and Sollano et al (1999) who have previously found that volume improves outcome. In addition to the effect of hospital volume on the outcomes for all cardiac patients, we make two more findings for the effect of volume on outcome.…”
Section: Aggregate Effects Of Focussupporting
confidence: 92%
“…This finding supports and extends the results from Peterson et al (2004), Halm et al (2002, Luft et al (1987) and Sollano et al (1999) who have previously found that volume improves outcome. In addition to the effect of hospital volume on the outcomes for all cardiac patients, we make two more findings for the effect of volume on outcome.…”
Section: Aggregate Effects Of Focussupporting
confidence: 92%
“…Our study, when put into context with others that suggest decreased morbidity in specialist centres, [4][5][6] makes the case for specialisation appear compelling.…”
Section: Resultssupporting
confidence: 59%
“…3 Recent suggestions have been made of associations between high patient volume and a decreased morbidity thus backing claims for specialist centres. [4][5][6] Developmental dysplasia of the hip is a specialist condition and its surgical treatment usually only occurs at tertiary centres. The development of avascular necrosis after the treatment of a developmental dysplasia of the hip is iatrogenic.…”
mentioning
confidence: 99%
“…All follow the Canadian Best Practice Recommendations for Stroke Care. 17 During the past few decades, there has been growing evidence that links increased patient volumes to improved outcomes in relation to complex medical and surgical procedures, including heart transplantation, 18 -25 but also increasingly for subspecialty clinics like anticoagulation clinics 24 and heart failure clinics. 25 However, the mechanisms by which these clinics result in improved outcomes remain elusive.…”
Section: Discussionmentioning
confidence: 99%